From China no. 3 to World no. 1 : the strategic practice of BNBM - Zhu, Yan; Li, Xiaohui; Zhang, Hong (London : Tsinghua University School of Economics and Management, 2017)
BNBM is a state owned enterprise that manufactures gypsum boards for the construction industry. The case examines how BNBM implemented a quality improvement system and transformed the enterprise from manufacturing 45 million square meters of gypsum boards in 2004 to 2.13 billion in 2016.
Originally Published InZhu, Y., Li, X., & Zhang, H. (2017). From China No. 3 to World No. 1: The Strategic Practice of BNBM. 8-817-312. Beijing, China: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bei xin jian cai (ji tuan) you xian gong si (China) -- Case studies; Strategic planning -- China -- Case studies; Drywall